2006
DOI: 10.1007/s10832-006-6258-8
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of cobalt oxide doped sintered ceria solid solutions

Abstract: The sintering of ceria solid solutions, such as Ce 0.9 Gd 0.1 O 1.95 (CGO10), is strongly promoted by the addition of 1 cat% of cobalt oxide, lowering the maximum sintering temperature by 200 • C and triplicating the maximum densification rate. This change in sintering behavior results from cobalt ion segregated at the grain boundaries. An average cobalt ion boundary coverage is at maximum 3.0 ± 1.9 at/nm 2 and is shown to depend on the cooling rate. Coverage by segregated gadolinium is also found and amounts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 37 publications
4
40
0
Order By: Relevance
“…In case of CoO additions, one has to keep in mind that in contrast to Gd 2 O 3 , the CoO has only a negligible solubility in CeO 2 and CGO20 47 and the CoO is concentrated in the grain boundaries, as has been reported in a previous study. 48 The increased boundary mobility is therefore due to a second phase with cobalt and gadolinium ions in excess in the grain boundaries. Obviously, a boundary layer rich in cobalt oxide acts as a fast diffusion path parallel to the grain boundary thus enhancing shrinkage during sintering.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In case of CoO additions, one has to keep in mind that in contrast to Gd 2 O 3 , the CoO has only a negligible solubility in CeO 2 and CGO20 47 and the CoO is concentrated in the grain boundaries, as has been reported in a previous study. 48 The increased boundary mobility is therefore due to a second phase with cobalt and gadolinium ions in excess in the grain boundaries. Obviously, a boundary layer rich in cobalt oxide acts as a fast diffusion path parallel to the grain boundary thus enhancing shrinkage during sintering.…”
mentioning
confidence: 99%
“…4, the solute drag effect of Gd persists at the boundary independent of the addition of cobalt oxide. It has been shown that the cobalt oxide grain boundary layer is sufficiently thin, 48 so that the mass transport across the grain boundaries is not hampered. The same conclusion was drawn in several grain growth studies of zirconia as summarized by Chen.…”
mentioning
confidence: 99%
“…SOFC systems have demonstrated one of the highest efficiencies (ranging from 40 to 70 %) of any power generation system, combined with very low environmental impact (virtually no acid gas or solid emissions). [42][43][44] The modular and solid state construction of SOFC devices allows flexibility to build stationary power generation plants in the 2 kW to hundreds of MW capacity range. [42] SOFCs are able to work not only with H 2 fuel, but also several hydrocarbons as CH 4 , alcohols and CO, giving rise to CO 2 and H 2 O as residue.…”
Section: Solid Oxide Fuel Cellsmentioning
confidence: 99%
“…[42] It is worthy to note the opposite behavior of the Tb doped sample, whose E a decreases when Co is added. It may be attributed to the partial incorporation of Co in the ceria solid phase and increasing in oxygen vacancy concentration as will be studied in detail in Chapter 5.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation